Penggunaan DAPT (Dual Antiplatelet) Pada CVA (Cerebrovascular Accident) Trombosis atau Stroke Iskemik dengan Riwayat PJK (Penyakit Jantung Koroner) - Putri, Rizky Ayu Artama; Badriah, Rani Nur; Anggraeni, Reta; Pratama, Jainuri Erik; Setiadi, Antonius Adji Prayitno; Herawati, Fauna; Gondokesumo, Marisca Evalina (Universitas Malahayati, 2024)
ABSTRACT Ischemic stroke is the sudden development of focal neurological deficit due to inadequate blood supply to an area of the brain, which can be thrombotic or embolic. CAD (Coronary Artery Disease) is pathological process characterized by the formation of atherosclerotic plaque followed by rupture, ulceration, or erosion. CAD can take the form of CCS (Chronic Coronary Syndrome). The 2018 AHA/ASA Guidline Antiplatelet Therapy used for ischemic stroke is Aspirin at a dose of 160mg-300mg 1x1. In the 2019 ESC Guidline, CCS patient therapy uses DAPT (Dual antiplatelet). In a 2021 AHA meta-analysis compared with aspirin alone, short-term DAPT within 24 hours after mild-moderate ischemic stroke reduced the risk of recurrent stroke at the expense of a higher risk of major bleeding. Here we present a case of a 76 year old female patient with ischemic stroke and CCS who used DAPT. Complaints of sluggishness, weakness in the left half of the body, acute dysarthria onset on the first day, when waking up. Hemiplegia S 1 week ago onset of waking up and being treated at Mataram Regional Hospital. The patient received the antiplatelet Aspirin 160mg 1x1 a day then switched DAPT (Aspirin 80mg 1x1 and Clopidogrel 75mg 1x1) due to a history of CCS. Keywords: CVA Thrombosis, Ischemic stroke, Aspilet, Clopidogrel, Coronary Artery Disease ABSTRAK Stroke iskemik adalah perkembangan fokal yang tiba-tiba terjadi defisit neurologis akibat suplai oksigen tidak memadai ke suatu area pada otak, dapat bersifat trombotik atau emboli. PJK (Penyakit Jantung Koroner) atau CAD (Coronary Artery Disease) adalah proses patologis ditandai dengan terbentuknya plak aterosklerotik diikuti dengan pecah, ulserasi, atau erosi. PJK dapat berupa penyakit CCS (Chronic Coronary Syndrome). Terapi Antiplatelet Guidline AHA/ASA 2018 yang digunakan pada stroke iskemik adalah Aspirin dosis 160mg-300mg 1x1. Pada Guidline ESC 2019 terapi pasien CCS digunakan DAPT (Dual antiplatelet). Pada meta analisis AHA 2021 dibandingkan dengan aspirin saja, DAPT jangka pendek dalam waktu 24 jam setelah stroke iskemik ringan-sedang mengurangi risiko stroke berulang dengan mengorbankan risiko perdarahan besar yang lebih tinggi. Berikut kami presentasikan sebuah kasus pasien Perempuan 76 tahun dengan Stroke Iskemik dan CCS yang menggunakan DAPT. Keluhann pelo, kelemahan separuh badan kiri, acute disartria onset hari pertama, saat bangun tidur. Hemiplegia S 1 minggu lalu onset bangun tidur di rawat di RSUD Mataram. Pasien menerima antiplatelet Aspirin 160mg 1x1 sehari lalu switch DAPT (Aspirin 80mg 1x1 dan Clopidogrel 75mg 1x1) karena Riwayat CCS. Kata Kunci: CVA trombosis, Ischemic stroke, Aspilet, Clopidogrel, Penyakit Jantung Koroner.